2015
DOI: 10.17559/tv-20141207160855
|View full text |Cite
|
Sign up to set email alerts
|

Distribution characteristics analysis of pressure-arch in horizontal stratified rocks under coal mining conditions

Abstract: Original scientific paper The criteria of separation and dislocation of the layered roof in mining are put forward through the simplified mechanical model with weak inter-layers. Considering five different variables, namely the number of layers, the distance from the weak inter-layers to the mine opening, the thickness of the weak inter-layers, the lateral pressure coefficient and the spacing of the bedding planes, the distribution characteristics of the pressure-arch in the horizontal stratified rocks are ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Dang et al (2021) used a numerical simulation to determine that the pressure distribution of hydraulic support in a simulated stope was rough "Λ" in the middle and both sides of the stope. Wang et al (2015) analyzed the distribution characteristics of the pressure arch of a horizontal layered rock mass in the process of coal seam mining and concluded that the lateral pressure coefficient had a significant influence on the pressure arch. Wang et al (2019b) established mechanical models for a symmetrical compression arch and concluded that upper broken rocks formed a symmetrical pressure arch in the near-field, and a far-field pressure arch formed in the mining field.…”
Section: Open Accessmentioning
confidence: 99%
“…Dang et al (2021) used a numerical simulation to determine that the pressure distribution of hydraulic support in a simulated stope was rough "Λ" in the middle and both sides of the stope. Wang et al (2015) analyzed the distribution characteristics of the pressure arch of a horizontal layered rock mass in the process of coal seam mining and concluded that the lateral pressure coefficient had a significant influence on the pressure arch. Wang et al (2019b) established mechanical models for a symmetrical compression arch and concluded that upper broken rocks formed a symmetrical pressure arch in the near-field, and a far-field pressure arch formed in the mining field.…”
Section: Open Accessmentioning
confidence: 99%
“…The macroscopic pressure arch was the macro bearing structure of the overburden rock in the mining field, and the bearing capacity of different forms was diversity. The pressure arch size of the surrounding rock in the far field affected the range of the overburden broken zone in the near field [3,5]. The alternating instability of the caving zone led to the occurrence of the strong (weak) weighting periodically during shallow coal mining [4].…”
Section: Geofluidsmentioning
confidence: 99%
“…The stability of the surrounding rock is the key problem which restricts the safety mining [1,2]. With the working face advancing, the pressure arch in the surrounding rock can be formed and the caving zone below the pressure arch can expand gradually [3]. Determination of the forming conditions and arching characteristics of the pressure arch in the mining field and analysing the nonuniform weighting mechanism on the working face during shallow coal mining with thick bedrock are the urgent problems to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a mining drill system, Jiang et al analysed pressure values applied during machining, and the effects of the intensity of cooling on cracks and breaks in natural stones [13]. Also in the case of mining-related machining, the damage processes of machined stone types were examined by Wang et al [14], who used a finite element simulation method. Revealing results were published by Zhai et al [15], who examined surface damaging and breaking effects of different frequency vibration waves in the case of granite materials.…”
Section: Literature Reviewmentioning
confidence: 99%